Drivers of technical excellence in the skills economy - James Relly, S; Robson, J; Emms, K; Laczik, A; Randhawa, A; Aizawa, I; Dong, L; Hwang, S; Pinto, V; Zlock, Z (WorldSkills UK, 2021)
With the UK government's intention to reinvigorate the further education sector (see Department for Education, 2019 commonly known as the Augar Report, and Skills for Jobs White Paper, DfE 2021 for England), learning from global insights is imperative, particularly of the ways other countries are developing and delivering technical excellence and the drivers used to achieve this. Skills competitions have been one way of doing this. WorldSkills Competitions (WSC) promote and enable skill development at the highest standard and have been shown to impact positively on the UK education and training system, and the economy more broadly (James Relly and Keep, 2018; Chankseliani, James Relly and Laczik, 2016). In the UK, during the last five to ten years, attention has been focused on the broader impact of WSC and Team UK to understand better how vocational excellence can, and is, developed. Further education, higher education and private training provider participation in skills competitions has grown across all four UK nations, with increasing numbers of students and apprentices joining Squad UK and/or Team UK and more of these institutions involved in local, regional and national competitions; at the same time the number of colleges hosting these skills competitions at various levels has also increased (James Relly, 2020). The ambitious plan clearly articulated in the Skills for Jobs White Paper (DfE, 2021) for England as well as policies being developed to improve standards in Wales, Scotland and Northern Ireland recognise the pivotal role TVET plays in skills development and boosting economic growth. With an increasing focus on specialisation and higher-level technical skills development (DfE, 2019) it is important to understand better how to develop technical excellence at all levels in the UK skills system and what drivers can be developed to do this. This report draws on distinctive insights into global skills systems. Innovations and developments in other countries have long held fascination for policymakers and educators in the UK. Indeed, an entire field of international and comparative education exists. While taking regard of the cultural and political contexts, looking to other countries to understand better their education and training system brings many advantages for policy learning and contextualised learning. This research endeavours to show how other countries enable technical and vocational education and training to be at the forefront of curriculum and workforce development. We address the following question: How do other countries, with interesting or pioneering technical education systems, develop the skills of their technical education workforce to ensure high quality teaching standards?